Quality of n-Type Czochralski Silicon Crystals for Solar Cells Grown from the Melt in Liquinert Crucibles. (5th October 2018) - Fukuda, Tetsuo; Horioka, Yukichi; Kariya, Nobumasa; Tanahashi, Katsuto; Takato, Hidetaka
Abstract : For the application to advanced high-performance solar cells, we have developed n-type CZ monocrystalline silicon crystals whose lifetime values are almost equal to those of MCZ silicon. We analyzed this point in detail, using the Shockley-Read-Hall model. In our growth, liquinert silica crucibles having non-wettable properties for molten silicon were employed in a conventional CZ puller. The improved lifetime is likely due to reduced carbon impurity. The CZ growth technique with liquinert crucibles brings a novel approach to the new CZ technique because it can supply higher-quality silicon compared to silicon grown by conventional CZ technique.